Mitotype Interacts With Diet to Influence Longevity, Fitness, and Mitochondrial Functions in Adult Female Drosophila - Towarnicki, Samuel G.; Ballard, J. William O. (Frontiers in Genetics, 2018)
Mitochondrial DNA (mtDNA) and the dietary macronutrient ratio are known to influence a wide range of phenotypic traits including longevity, fitness and energy production. Commonly mtDNA mutations are posited to be selectively neutral or reduce fitness and, to date, no selectively advantageous mtDNA mutations have been experimentally demonstrated in adult female Drosophila. Here we propose that a ND V161L mutation interacted with diets differing in their macronutrient ratios to influence organismal physiology and mitochondrial traits, but further studies are required to definitively show no linked mtDNA mutations are functionally significant. We utilized two mtDNA types (mitotypes) fed either a 1:2 Protein: Carbohydrate (P:C) or 1:16 P:C diet. When fed the former diet, Dahomey females harbouring the V161L mitotype lived longer than those with the Alstonville mitotype and had higher climbing, basal reactive oxygen species and elevated glutathione S-transferase E1 expression. The short lived Alstonville females ate more, had higher walking speed and elevated mitochondrial functions as suggested by respiratory control ratio, mtDNA copy number and expression of mitochondrial transcription termination factor 3. In contrast, Dahomey females fed 1:16 P:C were shorter lived, had higher fecundity, walking speed and mitochondrial functions. They had reduced climbing. This result suggests that mtDNA cannot be assumed to be a strictly neutral evolutionary marker when the dietary macronutrient ratio of a species varies over time and space and supports the hypothesis that mtDNA diversity may reflect the amount of time since the last selective sweep rather than strictly demographic processes.